Is Bhakti, a sine qua non for Mokṣa? A Psychospiritual exploration of Bhaktiśatak - Sadasivan, Anand; Parida, Tapan Kumar; H., Deepa (International Journal of Psychosocial Rehabilitation, 2020)
Vedānta suggests various paths for attaining Moksha. Jñānayoga, Rājayoga, Karmayoga, and Bhaktiyoga are the popular methods followed by spiritual seekers. Here, a well-established vedāntic ideology posits Jñāna to be the essential requirement for Mokṣa. A perusal of Bhakti literature would generate doubt about the vedāntic pronouncement of Jñāna, as an imperative for Mokṣa, and tends to oppose it, by suggesting Bhakti as the mandate. Bhaktiśatak is a chief work on Vedānta, composed by Kṛpālu ji Maharaj of the 20th century. Composed in a lucid style, in the Khariboli dialect of Hindi, Bhaktiśatak’s hundred verses enunciate Bhakti as the path that underpins all the other paths, and counsels one comfortably to Mokṣa. The goal of the current article is to scrutinise the paths of Jñāna and Bhakti, with reference to Bhaktiśatak and other major vedantic literatures like the Upaniṣad-s and the Bhagavadgītā. Overcoming māyā, the illusionary power of God, one attains Mokṣa. Bhaktiśatak propounds that māyā can only be overcome by the grace of God. The article therefore seeks clarity on the necessity of Bhakti for the attainment of Mokṣa. It further discusses the methods recommended by Kṛpālu ji to evoke Bhakti in a seeker.